2020
DOI: 10.1080/0960085x.2020.1740618
|View full text |Cite
|
Sign up to set email alerts
|

Examining the interplay between big data analytics and contextual factors in driving process innovation capabilities

Abstract: The potential of big data analytics in enabling improvements in business processes has urged researchers and practitioners to understand if, and under what combination of conditions, such novel technologies can support the enactment and management of business processes. While there is much discussion around how big data analytics can impact a firm's incremental and radical process innovation capabilities, we still know very little about what big data analytics resources firms must invest in to drive such outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(94 citation statements)
references
References 148 publications
(213 reference statements)
2
92
0
Order By: Relevance
“…Digital innovation research has used empirical and computational methodologies to study context (Gaskin et al, 2014;Majchrzak & Malhotra, 2016). The opportunity that arises is to embrace the methodological toolkit employed in digital innovation research, such as computational social science, or through configurational analysis as demonstrated by Mikalef and Krogstie (2020) in this special issue, within the development and evaluation of BPM technology. Likewise, researchers can draw on BPM technology (such as process mining or process analysis) to develop computational tools for analysing contextuality (Berente et al, 2019;Pentland et al, 2020b).…”
Section: Joining Forces Through Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital innovation research has used empirical and computational methodologies to study context (Gaskin et al, 2014;Majchrzak & Malhotra, 2016). The opportunity that arises is to embrace the methodological toolkit employed in digital innovation research, such as computational social science, or through configurational analysis as demonstrated by Mikalef and Krogstie (2020) in this special issue, within the development and evaluation of BPM technology. Likewise, researchers can draw on BPM technology (such as process mining or process analysis) to develop computational tools for analysing contextuality (Berente et al, 2019;Pentland et al, 2020b).…”
Section: Joining Forces Through Methodsmentioning
confidence: 99%
“…"Examining the Interplay Between Big Data Analytics and Contextual Factors in Driving Process Innovation Capabilities," by Mikalef and Krogstie (2020), explores how big data analytics interacts with BPM. Using survey data from 202 chief information officers and IT managers working in a diverse set of businesses, they distinguish configurations that support incremental versus radical process innovation.…”
Section: Can the Literatures On Digital Innovation And Business Process Management Come Together? Three Exemplarsmentioning
confidence: 99%
“…From a theoretical perspective, a positive impact of data analytics in general or associated topics on business value in organizations is widely accepted (Akhtar et al, 2019). Building on this, there are several approaches for showing potentials of data analytics in business environments (Akhtar et al, 2019;Gupta & George, 2016;Mikalef & Krogstie, 2020). Furthermore, research has already acquired extensive knowledge about data analytics competency and associated research fields (Debortoli et al, 2014;Shankararaman & Gottipati, 2016;Shirani, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Such resources and skills are typically found in medium-sized to large organizations in the product and/or service industry. This is because medium-sized or large organizations tend to have a well-developed process orientation (Harmon and Wolf 2018 ; Mikalef and Krogstie 2020 ; Neubauer 2009 ), which is presupposed for the use of our method. As we will show in Sect.…”
Section: Design Specificationmentioning
confidence: 99%